2019
DOI: 10.24926/jcotr.v9i1.2535
|View full text |Cite
|
Sign up to set email alerts
|

The College Choice Process of African American and Hispanic Women

Abstract: Studies examining access and college participation have generally focused on racial and ethnic minorities as a group. This study qualitatively examined the college choice process for African American and Hispanic females. Through the voices of these women, three major themes that support their decision to attend college were identified. All study participants were from a single, case study large Southwestern university.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Though literature on college “choice” is extensive, empirical research on Black women’s college “choice” is far less common. Within the scant literature, empirical studies on Black women’s college decisions have focused on the roles of parental influence and schools (Butner et al 2001 ; Horvat 1997 ; Muhammad and Dixson 2008 ; Muhammad et al 2008 ; Smith 2008 ). Notably, most studies on Black women’s college decision focus on the differences in college enrollment between Black women and Black men (Smith and Fleming 2006 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Though literature on college “choice” is extensive, empirical research on Black women’s college “choice” is far less common. Within the scant literature, empirical studies on Black women’s college decisions have focused on the roles of parental influence and schools (Butner et al 2001 ; Horvat 1997 ; Muhammad and Dixson 2008 ; Muhammad et al 2008 ; Smith 2008 ). Notably, most studies on Black women’s college decision focus on the differences in college enrollment between Black women and Black men (Smith and Fleming 2006 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Campus racial climate is also an important consideration for African American students when they choose postsecondary institutions (Allen, College Access and Choice Processes 1987;Butner et al, 2001;Cho, Hudley, Lee, Barry, & Kelly, 2008;Litten & Hall, 1989;McDonough, Antonio, & Trent, 1997). Employing a web-based survey, Cho et al (2008) found that acceptance of racial diversity was more important to first-generation college-going African Americans and Latinos than to students of other races.…”
Section: African American Students and College Choicementioning
confidence: 99%